LIPID METABOLISM DISORDERS IN PATIENTS WITH CHRONIC HEPATITIS C - L. I. Tkachenko; V. V. Maleev; D. M. Sarieva (Архивъ внутренней медицины)
Purpose of the study. To study lipid metabolism in chronic hepatitis C and to assess its impact on the formation of insulin resistance, steatosis and progression of liver fibrosis.Materials and methods. The study included 205 patients with chronic hepatitis C (CHC). Conducts research, depending on the genotype C, viral load and body mass index (BMI) of the patients.Results. CHC patients revealed a combined hyperlipoproteinemia on the background of op-pression synthesis of apolipoproteins A1 and B. Formation of hepatic steatosis was associated with HCV genotype 3 virus-induced viral load at ≥ 6 log10 IU/ml and metabolic in VL < 6 log10 IU/ml. In patients with chronic hepatitis C genotype 1, high viral load leads to inhibition of protein synthesis conveyor ApoA1 and increased synthesis of cholesterol, accompanied by abdominal obesity and the formation of insulin resistance. CHC patients with BMI < 25 kg/m2 viral load ≥ 6 log10 ME/ml was associated with dyslipidemia IV type on D. Fredriskson (1970), hyperglycemia, insulin resistance and diabetes. The advanced stage of liver fi brosis (F ≥ 3 on a scale METAVIR) and non-response to treatment were associated with a decrease in HDL cholesterol below normal. With an increase in viral load > 5 log10 ME/ml signifi cantly increased the risk of lipid and carbohydrate metabolism.